Effective structure of financial resources as basis of development of an industrial complex of Russia (Путеводитель предпринимателя, 2020)
Financial resources are the subject of a common system of financial management of the company, one ofwhose tasks is to take decisions on the aggregate formation and functioning of the optimal structure of financial resources in order to increase and maximize the profits of the enterprise. To some extent, the financial potential of acting as a lever, which forms the mechanism of dynamic transformation of resources as a result of the company. Equally important is its role in the reproductive processes of the enterprise.